Pengaruh Kinerja Keuangan Terhadap Financial Distress Perusahaan Asuransi di Indonesia Sebelum dan Saat Pandemi Covid-19 - Maysaroh, Watim; Suhendro, Saring; Dewi, Fajar Gustiawaty (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p18, 2022)
The purpose of the study was to determine the effect of profitability, liquidity, and leverage on financial distress and to determine the financial distress condition of insurance companies on the IDX before and during the pandemic. The sample used purposive sampling method on 15 insurance companies in Indonesia. The test was carried out using multiple linear regression with SPSS 25. The results showed that ROE and CR had no significant effect on financial distress. Meanwhile, DAR has a significant negative effect on firm value. The Z-Score shows that the Harta Aman Pratama Tbk (AHAP) Insurance company experienced financial distress before Covid-19 and was in the gray area category at the time of Covid-19. Meanwhile, Malaca Trust Wuwungan Insurance Tbk (MTWI) is in the gray area category during the Covid-19 period and during the Covid-19 period. Keywords: Financial Distress; Profitability; Liquidity; Leverage; Altman Z-Score.